Au@MOF-199 functionalized graphene oxide nanocomposite for simultaneous electrochemical detection of dopamine and uric acid - Zhou, Feng; Lim, Hong Ngee; Ibrahim, Izwaharyanie; Liu, Yi; Qin, Danfeng (Elsevier B.V., 2026)
Simultaneous detection of dopamine (DA) and uric acid (UA) in biological fluids is critical for diagnosing neurological and metabolic disorders. However, traditional enzymatic sensors are plagued by enzyme denaturation, limited shelf life, and poor batch-to-batch reproducibility. To address these limitations, a nonenzymatic electrochemical sensor based on a graphene oxide-gold nanoparticle-MOF-199 (GO-Au@MOF-199) nanocomposite was developed to simultaneously detect DA and UA. The ternary hybrid material was synthesized via a solvothermal method, leveraging the high surface area of MOF-199, the excellent catalytic activity of Au nanoparticles, and the superior electron transport properties of GO. The designed GO-Au@MOF-199 composites possess a large surface area (205 m2 g−1), exhibiting excellent electroanalytical capability for the detection of DA and UA. This innovative sensor, constructed on screen-printed electrodes (SPEs), exhibited distinct cathodic peak separation for DA and UA, enabling selective and sensitive dual-analyte detection. The sensor exhibited a wide linear detection range (0.1–100 μM) along with low limits of detection (LODs) of 16 nM for DA and 25 nM for UA, as well as high sensitivities of 2001 μA mM−1 cm−2 (for DA) and 1281 μA mM−1 cm−2 (for UA). Moreover, the sensor exhibited excellent operational stability (<7 % signal loss after 1000 cycles) and high recovery rates (95.7–112.9 %) in spiked urine samples, confirming its robustness and applicability for real biological samples. This work presents a robust and efficient sensing platform, showcasing the synergistic integration of nanomaterials for real-time analysis, with strong potential for point-of-care diagnostics and clinical monitoring of metabolic biomarkers.